Cognitive function, health-related quality of life, and symptoms of depression and anxiety sensitivity are impaired in patients with the postural orthostatic tachycardia syndrome (POTS) - Anderson, Jake W.; Lambert, Elisabeth A.; Sari, Carolina I.; Dawood, Tye; Esler, Murray D.; Vaddadi, Gautam; Lambert, Gavin W. (Frontiers in Physiology, 2014)
The Postural Orthostatic Tachycardia Syndrome (POTS) is a condition in which heart rate increases abnormally when the individual assumes an upright position. In addition to the marked tachycardia, presyncope and syncope, patients with POTS often complain of light-headedness, fatigue and difficulty in concentrating. The present study assessed individuals with POTS for psychiatric comorbidity, anxiety sensitivity and health related quality of life and examined general cognitive ability. Data was obtained from patients with POTS (n=15, 12 female, aged 30±3 years) and age matched healthy subjects (n=30, 21 female, aged 32±2 years). Patients with POTS commonly presented with symptoms of depression, elevated anxiety and increased anxiety sensitivity, particularly with regards to cardiac symptoms, and had a poorer health related quality of life in both the physical and mental health domains. While patients with POTS performed worse in tests of current intellectual functioning (verbal and non-verbal IQ) and in measures of focused attention (digits forward) and short term memory (digits back), test results were influenced largely by years of education and the underlying level of depression and anxiety. Acute changes in cognitive performance in response to head up tilt were evident in the POTS patients. From results obtained, it was concluded that participants with POTS have an increased prevalence of depression and higher levels of anxiety. These underlying symptoms impact on cognition in patients with POTS, particularly in the cognitive domains of attention and short-term memory. Our results indicate that psychological interventions may aid in recovery and facilitate uptake and adherence of other treatment modalities in patients with POTS.